A History of Violence - Walcott, Rinaldo (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Rinaldo Walcott discusses how the convergence of police violence and COVID-19 on George Floyd’s body encapsulates a history of violence that Black people collectively experience in North America. Walcott unpacks how, in the midst of a pandemic and under stringent restrictions on movement and gathering in groups, George Floyd was murdered publicly for allegedly passing a counterfeit twenty-dollar bill. His murder by police tells a story of the kind of society in which we collectively reside and the necessary changes that need to be made to achieve justice for all.